Spiritualitas Postmodern yang Diversitas: Sebuah Pembacaan City of God Karya Agustinus - Fransina Wattimena; Yohanes Eko T; Yusuf Kurniawan E (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2023)
Human life throughout history has never been devoid of spiritual struggles, even in the current postmodern era. The postmodern era is characterized by its recognition of diverse perspectives. The very nature of this diversity makes the postmodern era inherently relative and subjective. Consequently, the postmodern era is seen as a challenge to Christianity, which emphasizes final and absolute truth. This article aims to bridge the gap between postmodernism with its diversity and Christianity with its Christian spirituality that respects various sacred authorities. The experiences of Augustine, who, on one hand, affirmed various beliefs of his time while remaining rooted in the foundational teachings of early Christianity, serve as a significant spiritual model in the postmodern era. Specifically, Augustine's work, "City of God," is employed. Using hermeneutical methods, the researcher reexamines Augustine's spirituality and attempts to implement it as a model of postmodern spirituality. The ultimate thesis of this research is that "City of God" generates a dual spirituality, one that embraces diversity while also remaining firmly rooted in its faith tradition.